Pengaruh Corporate Governance terhadap Efisiensi Bank Umum Syariah di Indonesia - Jamil, Muhammad; Refi, Teuku Muana (Lembaga KITA, 2020)
This study analyzes the functional relationship between the efficiency of Islamic Commercial Banks (BUS) and the implementation of good corporate governance (GCG) as a variable predictor. Using panel dataset of 6 BUS listed on the Indonesia Stock Exchange during the 2014-2018 period, the fixed effect panel regression model was used to analyze the relationship between variables. This study proves that the simultaneous implementation of GCG consisting of the proportion of share ownership, size of board, and board composition have a significant effect on the efficiency of BUS. Partially, the proportion of share ownership and the boad composition have a positive and significant effect, on the other hand, the board size has no significant effect on the efficiency of BUS.Â Keywords: Efficiency of sharia commercial bank, implementation of GCG and panel regression